Records of the Indian Pangolin (Mammalia: Pholidota: Manidae: Manis crassicaudata) from Mansehra District, Pakistan - Tariq Mahmood; Konish Kanwal; Iftikhar-Uz Zaman (Journal of Threatened Taxa, 2018)
This study investigated records of distribution and population density of the Indian Pangolin Manis crassicaudata in Mansehra District, Pakistan.  Field surveys were conducted from September 2015 to August 2016 to record direct and indirect signs of the species, including burrows and faecal matter.  Information was also collected from local people through unstructured interviews.  Our results show that the Indian Pangolin occurred at two sampling sites only (Lassan Nawab and Paras) in the study area.  We recorded low numbers of burrows (feeding and permanent burrows) at these two sites.  One direct field sighting of one individual was made at Paras.  A low mean population density of 0.28±0.45 per km2 was estimated at seven different selected sites, but for the district as a whole, the population density was as low as 0.00044 individuals per km2.  This study recommends initiating conservation efforts in the study area to further understand and conserve the remaining population of Indian Pangolin in Mansehra District.